Export boosting policies and firm performance: Review of empirical evidence around the world - Stjepan Srhoj; Vanja Vitezić; Joachim Wagner (Journal of Economics and Statistics, 2023)
How effective are government policy attempts to boost firm exports in the short-run? We answer this question by conducting a review of 33 studies from 26 countries around the world, and provide nine findings. Export boosting policies are defined as a group of public policies that aim to increase firm exports in the short-run. These include policies such as export promotion, export-oriented public grants, public export guarantee schemes and subsidised export loans. Our review provides insights into policy effectiveness with respect to extensive and intensive export margins, as well as firms' production function inputs and its outputs. The heterogeneity of effects across firm characteristics is emphasised, and the discussion is enriched with new evidence of spillover effects from export boosting policies. Finally, we summarise back-of-the-envelope calculations of the cost-benefit analysis and provide recommendations for future research.
Keywords: F13; F14; L15; L25; O10; O24; 330; export promotion policies; grants; guarantees; impact evaluation; loans; review